Strategic Lawsuits Against Public Participation in a Cross-Border Context: Anti-SLAPP Legislation and the Role of the Private International Law Regimes in the EU and England - Gábor Levente Kozma; Murilo Lubambo de Melo (Netherlands International Law Review, 2026)
Abstract In recent years, strategic lawsuits against public participation (SLAPPs) have gained increasing global attention. In response, several jurisdictions have adopted legislative measures to curtail abusive litigation tactics targeting individuals engaged in public participation. This paper contributes to the academic dialogue by critically examining the capabilities of two legal systems to constrain the use of SLAPPs in the cross-border context: the legal system of the European Union, and of England and Wales. The analysis approaches the topic from the perspective of private international law, with particular emphasis on jurisdictional and recognition and enforcement rules. The paper first examines the current jurisdictional framework of the Brussels I Recast Regulation and highlights the need for reform. The study furthermore examines the recently adopted EU Anti-SLAPP Directive, with specific attention to the private international law instruments it offers. It also analyses the judgement of the Court of Justice of the European Union in Real Madrid v. Le Monde , which presents a new avenue for curtailing SLAPPs within the EU internal market. The second part of the paper focuses on the legal system of England and Wales, reviewing the effectiveness of the English common law and procedural rules in relation to international jurisdiction and the modified regime after the Defamation Act 2013. It highlights the potential role of the forum non conveniens doctrine, and the Economic Crime and Corporate Transparency Act 2023. Finally, it explores the potential of the English common law rules on recognition and enforcement as an additional recourse against SLAPPs. To conclude, the paper argues that both systems offer tools that can be fine-tuned to better address the challenges of SLAPPs.